Prevalence of underweight, overweight and obesity among children and adolescents in Germany. KiGGS Wave 2 results according to international reference systems - Anja Schienkiewitz; Stefan Damerow; Angelika Schaffrath Rosario (Journal of Health Monitoring, 2018)
In Germany, the reference system according to Kromeyer-Hauschild is usually used to define underweight, overweight and obesity in children and adolescents. International classification systems to describe prevalence are the reference systems of the World Health Organization (WHO) and the International Obesity Task Force (IOTF). This article reports underweight, overweight and obesity prevalences among children and adolescents according to WHO and IOTF criteria using data from the second wave of the German Health Interview and Examination Survey for Children and Adolescents (KiGGS Wave 2, 2014-2017). According to the WHO reference system, the prevalence of underweight among 5- to 17-year-olds is 1.6%, the prevalence of overweight is 26.3% (including obesity) and the prevalence of obesity is 8.8%. According to IOTF, the prevalence of underweight among 3- to 17-year-olds is 10.0%. The prevalence of overweight (including obesity) is 19.3% and the prevalence of obesity is 4.7%. From a public health point of view, underweight as an indicator of malnutrition plays a rather minor role in Germany. The prevalence of overweight according to WHO is three quarters higher and one quarter higher according to IOTF than the national reference. When comparing the international reference systems, the WHO prevalence is one third higher than IOTF prevalence. According to national and international reference systems, no further increase in the prevalence of overweight and obesity is observed, but the prevalence remain at a high level.